Dynamics at an Intermediate-Macroeconomics Level: A Keynesian Macroeconomic Model with Inventory and Production-Consumption Delays - Vasilev, Aleksandar (Theoretical and Practical Research in Economic Fields; Vol 17 No 2 (2026): TPREF Volume XVII Issue 2(38) June 2026DO - 10.14505/tpref.v17.2(38).20, 2026)
We present a dynamic Keynesian model at an intermediate macroeconomic level, a la Metzler (1941) and Leslie (1993), where the utilized propagation mechanism is firms' inventory management, and producers following adaptive expectations in order to meet stochastic demand. In addition, there is a delay between production, and subsequent delivery and consumption from the shelves. The discrete-time model generates a second-order linear difference equation, which exhibits endogenous cycles, with fluctuations (oscillations), which - for a plausible range of model parameters – are stable, and die out over time. Pedagogically, this is the simplest model that is able to generate interesting non-linear dynamics, and thus of interest to both undergraduate economics students, and instructors teaching intermediate macroeconomics.